Stock the Sticks Business Game : a market simulation experience at UMK (University Malaysia Kelantan) stock the sticks : business at Class CASE SERIES - 'A' - Naila Aaijaz; Mohamed Dahlan Ibrahim (2011)
“Hey! He made a mistake, exclaimed the students in audience . Yes, mistake it was, indeed as the student playing a supply-chain-management business game (also called distribution game) had not stocked any inventory and to add to the problem, had landed with a backlog of orders. But in a class while playing a business game it will just be a penalty but when it comes to an actual business site, it will be a disaster losing one’s share, profits etc. It is based on two novel elements, Problem Based Learning (PBL) and Market Simulation Game, Stock the Stick Business Game. PBL serves as the learning approach and the market simulation game as the source of the (real time) problem set on which the learning approach is anchored. The main part of the course is designed as group work. Each team manages a single firm and sets its individual project and learning agenda. Formal problems are given to the teams in order to direct their learning process.